Snake Venoms in Diagnostic Hemostasis and Thrombosis - Moore, Gary William (Seminars in Thrombosis and Hemostasis, 2021)
Snake venoms have evolved primarily to immobilize and kill prey, and consequently, they contain some of the most potent natural toxins. Part of that armory is a range of hemotoxic components that affect every area of hemostasis, which we have harnessed to great effect in the study and diagnosis of hemostatic disorders. The most widely used are those that affect coagulation, such as thrombin-like enzymes unaffected by heparin and direct thrombin inhibitors, which can help confirm or dispute their presence in plasma. The liquid gold of coagulation activators is Russell's viper venom, since it contains activators of factor X and factor V. It is used in a range of clotting-based assays, such as assessment of factor X and factor V deficiencies, protein C and protein S deficiencies, activated protein C resistance, and probably the most important test for lupus anticoagulants, the dilute Russell's viper venom time. Activators of prothrombin, such as oscutarin C from Coastal Taipan venom and ecarin from saw-scaled viper venom, are employed in prothrombin activity assays and lupus anticoagulant detection, and ecarin has a valuable role in quantitative assays of direct thrombin inhibitors. Snake venoms affecting primary hemostasis include botrocetin from the jararaca, which can be used to assay von Willebrand factor activity, and convulxin from the cascavel, which can be used to detect deficiency of the platelet collagen receptor, glycoprotein VI. This article takes the reader to every area of the diagnostic hemostasis laboratory to appreciate the myriad applications of snake venoms available in diagnostic practice.
Keywords: coagulation assays; hemostasis; Russell's viper venom; snake venom toxins; snake venom thrombin-like enzymes